Responses of aquatic macroinvertebrates to human pressure in a tropical highland volcanic basin: Birrís River, Irazú Volcano (Costa Rica) - Vásquez, Danny (2018)
Background. Tropical mountain rivers are strategic sources of water for human development while biological communities are indicators of the status of these ecosystems. However, volcanic basins close to large urban areas are affected by increasing human pressures that threaten the future of these ecosystems and their benefts to society. Goals. This paper analyzes the evolution of the responses of the aquatic macroinvertebrate assemblages in the face of increasing pressures in the Birrís River basin, which is essential for providing food and energy for the Greater Metropolitan Area of Costa Rica. The hypothesis that volcanic headwater communities are highly vulnerable to human impacts was tested. Methods. Composition and structure of aquatic macroinvertebrate assemblages were assessed along main river channels over two years. Results. The spatial variability of assemblages was related to organic pollution and the self-purifcation capacity of the river. Temporal variability was mainly explained by the intra-annual climate variability (seasonality). Macroinvertebrate assemblages were dominated by Chironomidae (Diptera), Simuliidae (Diptera), and Baetidae (Ephemeroptera) throughout the year. High ﬂows during the rainy season (May to December) reduced density while diversity peaked at the end of that season. Ephemeroptera and Trichoptera reached their maximum abundance during the dry season, while Diptera showed maximum richness at the end of the rainy season. Conclusions. Biological communities showed spatial and temporal adaptations to the main environmental stresses, including high levels of organic pollution. However, the high slope of river channels favors the self-purifcation processes, which offer an opportunity for the recovery of ecological integrity combined with control of the organic discharges. More information is needed on taxonomy and autoecology of aquatic fauna and ﬂora in these fragile volcanic environments that are strategic for the protection of water resources in the tropics.